2015
DOI: 10.1080/10911359.2014.956961
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Small Entrepreneurs Through a Microcredit Program in Penang, Malaysia: A Case Study

Abstract: Microcredit has been recognized as one of the most efficient tools for alleviating poverty by the United Nations considering its significant contribution in terms of job creation and revenue generation for governments. Microcredit programs can change the lives of people and revitalize communities in the world's poorest as well as the richest countries. This study looks at 350 entrepreneurs who joined the scheme of various microcredit programs in Penang, Malaysia. In this study, findings have been obtained that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Their programmes are proven to improve rural enterprise, skills, confidence, and social standing among rural women (Chan & Abdul Ghani, 2011). Besides individual improvements, MFIs are found to increase entrepreneurs’ income and fulfil their basic need (Hassan & Ibrahim, 2015). In terms of the quality of life between MFI old and new participant, old participants live in bigger houses.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their programmes are proven to improve rural enterprise, skills, confidence, and social standing among rural women (Chan & Abdul Ghani, 2011). Besides individual improvements, MFIs are found to increase entrepreneurs’ income and fulfil their basic need (Hassan & Ibrahim, 2015). In terms of the quality of life between MFI old and new participant, old participants live in bigger houses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Malaysia, microfinance is critical to the socio-economic development of the low-income and poor households. Previous studies have found that microfinance initiatives include increasing microenterprise assets of the hardcore poor households (Al Mamun, Wahab, & Malarvizhi, 2010); improving the quality of life of the borrowers (Al Mamun, Adaikalam, Mazumder, & Wahab, 2011); increasing employment opportunities at both community and household levels (Al Mamun, Wahab, & Malarvizhi, 2011); having a positive impact on total productive assets and the number of gainfully employed (Al Mamun, Malarvizhi, Hossain, & Wahab, 2011); encouraging the development of rural enterprises, skills, and confidence and social standing of rural women (Chan & Abdul Ghani, 2011); significantly related to MSE performance (Mahmood & Mohd Rosli, 2013); affecting the development of formal bonding social capital (Al Mamun, 2014); decreasing the level of economic vulnerability (Al Mamun, Mazumder, & Malarvizhi, 2014); increasing household income and reducing both poverty and level of economic vulnerability (Al Mamun & Mazumder, 2015); increasing income and fulfilling basic needs of entrepreneurs (Hassan & Ibrahim, 2015); having a positive impact on household income (Samer et al, 2015); affecting women’s monthly income and empowering them in household decision making (Al-Shami, Razali, & Rashid, 2017) and positively affecting borrowers household income and personal assets acquisition (Al-Shami, Majid, Mohamad, & Rashid, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Their programs have been proven to improve rural enterprise and social standing among rural women (Chan and Abdul Ghani, 2011). Besides individual improvement, MFIs are found to increase entrepreneurs' income and fulfill their basic needs (Hassan and Ibrahim, 2015). In terms of the quality of life between MFI old and new participants, old participants live in bigger houses.…”
Section: Low-income Householdsmentioning
confidence: 99%
“…Regulators, who historically have had the function of regulating and monitoring financial system management (Ardic et al , 2011), are now targeting the issue of expansion of financial access. As an example, the studies of Panjaitan-Drioadisuryo and Cloud (1999), Nair (2001), Sanyal (2009), Hassan and Ibrahim (2015) underline that political and governmental strategy plays a relevant role in financial inclusion, as everyone should have access to financial resources and no barriers should exist to limit financial services accessibility (Hannig and Jansen, 2010).…”
Section: A Brief Review Of the Theoretical Background On Financial Inclusionmentioning
confidence: 99%